ظواهر لغوية في اللهجة السورية - قشقش، رنيم محمد ضياء; بخيت، محمد إبراهيم محمد (جامعة المدينة العالمية, 2023)
يقوم هذا البحث على دراسة الظواهر اللغوية في اللهجة السورية، والبيان الاستقرائي لها في كل من الهمز والقلب المكاني والنحت، بحيث تم التناول لها في دراسة تأصيلية لغوية، ومشكلة البحث في تناول الظواهر اللغوية في اللهجة السورية بهدف رصد قواعدها وضوابط تصريفها واشتقاقها، وتأصيلها وربطها مع أصولها العربية الفصيحة، ويظل التوقف عند اللهجات المحكية ضرورةً ملحّةً لفهم واقعها، وتركيباتها واشتقاقاتها، وإيجاد الروابط والصلات بينها، والاطلاع على ظواهرها اللغوية وتأصيلها علميًا. وتهدف الدراسة إلى تحقيق التعرف على التطور الدلالي للهجات السورية وارتباطه بالفصحى، والتحليل للخصائص الصوتية للهجات السورية، واستقراء ظواهر النحت والقلب المكاني والهمز في اللهجات السورية وتأثيراتها على اللهجات السورية، والتعرف على مدى تأثير اللغة الفصحى وانعكاسها على اللهجات السورية، وتمثل منهج الدراسة: في استخدام الباحثة المنهج الوصفي والمنهج التحليلي؛ فضلاً عن المنهج التاريخي في عرض التطور الدلالي؛ وقد وصلت الباحثة لمجموعة من النتائج المختلفة ومن أهمها: وجود بعض الفروق في أداء ونطق الكلمات بين كل بلدة وغيرها داخل المحافظة الواحدة في سوريا، ووجود بعض التمايز اللغوي بين أهل المدينة والريف في بعض الظواهر القليلة. This research focuses on linguistic phenomena in the Syrian dialect, specifically accentuation, metathesis, and linguistic blending. The aim is to conduct an original linguistic study and highlight the importance of preserving the standard language and its various aspects, such as phonetics, morphology, grammar, semantics, and derivation, to prevent them from disappearing or changing. However, it is also crucial to study spoken dialects in order to understand their reality, combinations, and derivations, and to establish links and connections between them. By doing so, we can scientifically analyze their linguistic phenomena and trace their roots. The objective of this study is to identify the semantic development of Syrian dialects and how they relate to the standard language. Additionally, the study aims to analyze the phonetic characteristics of Syrian dialects, explore linguistic blending, metathesis, and accentuation phenomena in the Syrian dialects, and evaluate their effects on the language. The study also aims to examine the extent of the influence of the standard language on the Syrian dialects. To achieve these goals, the researcher utilized a descriptive analytical approach. The study yielded several findings, the most noteworthy of which include the existence of differences in the pronunciation and usage of words between different towns within the same governorate in Syria. Furthermore, the study identified some linguistic distinctions between city dwellers and those residing in rural areas, but only in a few phenomenon
Keywords: الظواهر اللغوية -- اللهجات العربية -- اللهجات السورية